If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n(2 + -1n) = -11 (2 * 5n + -1n * 5n) = -11 (10n + -5n2) = -11 Solving 10n + -5n2 = -11 Solving for variable 'n'. Reorder the terms: 11 + 10n + -5n2 = -11 + 11 Combine like terms: -11 + 11 = 0 11 + 10n + -5n2 = 0 Begin completing the square. Divide all terms by -5 the coefficient of the squared term: Divide each side by '-5'. -2.2 + -2n + n2 = 0 Move the constant term to the right: Add '2.2' to each side of the equation. -2.2 + -2n + 2.2 + n2 = 0 + 2.2 Reorder the terms: -2.2 + 2.2 + -2n + n2 = 0 + 2.2 Combine like terms: -2.2 + 2.2 = 0.0 0.0 + -2n + n2 = 0 + 2.2 -2n + n2 = 0 + 2.2 Combine like terms: 0 + 2.2 = 2.2 -2n + n2 = 2.2 The n term is -2n. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2n + 1 + n2 = 2.2 + 1 Reorder the terms: 1 + -2n + n2 = 2.2 + 1 Combine like terms: 2.2 + 1 = 3.2 1 + -2n + n2 = 3.2 Factor a perfect square on the left side: (n + -1)(n + -1) = 3.2 Calculate the square root of the right side: 1.788854382 Break this problem into two subproblems by setting (n + -1) equal to 1.788854382 and -1.788854382.Subproblem 1
n + -1 = 1.788854382 Simplifying n + -1 = 1.788854382 Reorder the terms: -1 + n = 1.788854382 Solving -1 + n = 1.788854382 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + n = 1.788854382 + 1 Combine like terms: -1 + 1 = 0 0 + n = 1.788854382 + 1 n = 1.788854382 + 1 Combine like terms: 1.788854382 + 1 = 2.788854382 n = 2.788854382 Simplifying n = 2.788854382Subproblem 2
n + -1 = -1.788854382 Simplifying n + -1 = -1.788854382 Reorder the terms: -1 + n = -1.788854382 Solving -1 + n = -1.788854382 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + n = -1.788854382 + 1 Combine like terms: -1 + 1 = 0 0 + n = -1.788854382 + 1 n = -1.788854382 + 1 Combine like terms: -1.788854382 + 1 = -0.788854382 n = -0.788854382 Simplifying n = -0.788854382Solution
The solution to the problem is based on the solutions from the subproblems. n = {2.788854382, -0.788854382}
| x+6=2x-6 | | -353=5(3+8x)+6 | | z-15.5=-5.1 | | 5b+45=5b+45 | | 4x-7/3=3 | | 5(3y+4)=50 | | 5t+32=102 | | 70+x-180=191 | | 70-x-180=191 | | z/4-z=6 | | 9x+1.5=0.75 | | x+4/3=5 | | 10=3n-4+5 | | 7(x+4)+5=10x-3(x-5) | | 7x+21=205 | | 0.5(y+1)=9 | | 3y-11=9-y | | 18x-8=4x-3 | | ln(4x)=2ln(7x) | | 6g+2(-6+3g)=1-g | | 3(7x-1)=22x | | 2x+6=6-4x | | 12(x+4)=4(3x+1)+44 | | 8+3x=0 | | r+(-0.16)=0.37 | | x+15+2x=-20-2x-25 | | 5d-8d-4=-4+3d | | 21+x=5-3x | | 13y+2(7y+5)=118 | | 45=4t-13t | | 5(6x-x)=0 | | x+20+2x=-2-2x-8 |